Intelligent data analytics for terror threat prediction architectures, methodologies, techniques and applications - Pani, Subhendu Kumar 1980-; Singh, Sanjay Kumar; Garg, Lalit 1977- (Wiley, 2021)
Rumor Detection and Tracing its Source to Prevent Cyber-Crimes on Social Media / Ravi Kishore Devarapalli, Anupam Biswas -- Internet of Things (IoT) and Machine to Machine (M2M) Communication Techniques for Cyber Crime Prediction / Jaiprakash Narain Dwivedi -- Crime Predictive Model Using Big Data Analytics / Hemanta Kumar Bhuyan, Subhendu Kumar Pani -- The Role of Remote Sensing and GIS in Military Strategy to Prevent Terror Attacks / Sushobhan Majumdar -- Text Mining for Secure Cyber Space / Supriya Raheja, Geetika Munjal -- Analyses on Artificial Intelligence Framework to Detect Crime Pattern / R Arshath Raja, N Yuvaraj, NV Kousik -- A Biometric Technology-Based Framework for Tackling and Preventing Crimes / Ebrahim AM Alrahawe, Vikas T Humbe, GN Shinde -- Rule-Based Approach for Botnet Behavior Analysis / Supriya Raheja, Geetika Munjal, Jyoti Jangra, Rakesh Garg -- Securing Biometric Framework with Cryptanalysis / Abhishek Goel, Siddharth Gautam, Nitin Tyagi, Nikhil Sharma, Martin Sagayam -- The Role of Big Data Analysis in Increasing the Crime Prediction and Prevention Rates / Galal A AL-Rummana, Abdulrazzaq H A Al-Ahdal, GN Shinde -- Crime Pattern Detection Using Data Mining / Dipalika Das, Maya Nayak -- Attacks and Security Measures in Wireless Sensor Network / Nikhil Sharma, Ila Kaushik, Vikash Kumar Agarwal, Bharat Bhushan, Aditya Khamparia -- Large Sensing Data Flows Using Cryptic Techniques / Hemanta Kumar Bhuyan -- Cyber-Crime Prevention Methodology / Chandra Sekhar Biswal, Subhendu Kumar Pani
Includes bibliographical references and index
Keywords: Computerunterstützte Kommunikation; Datenanalyse; Data Mining; Gefahrenabwehr; Attentat; Terrorismus; Terrorism / Prevention; Computer networks; Data mining; Terrorism; Prevention; Aufsatzsammlung